2023
DOI: 10.1257/jel.20221632
|View full text |Cite
|
Sign up to set email alerts
|

Cash Is Alive: How Economists Explain Holding and Use of Cash

Oz Shy

Abstract: Research on holding and use of cash involves many aspects, such as reasons for holding and hoarding cash, transactional demand for cash, cash management, type of spending paid with cash, type of consumer who pays cash, merchant acceptance, how consumers get cash, currency denominations, legal aspects, cash substitutes, and cost of cash. The purpose of this article is to introduce the reader to some of the research economists do on consumer holding and use of cash. (JEL D11, D12, E26, E31, E41, E42)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 168 publications
0
1
0
Order By: Relevance
“…In a recent review article, Shy (2023) showed the main research trends in the use of cash by consumers when choosing a payment method. He outlined several reasons why people opted to pay cash.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In a recent review article, Shy (2023) showed the main research trends in the use of cash by consumers when choosing a payment method. He outlined several reasons why people opted to pay cash.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%